A 4,500‐Year‐Long Record of Southern Rocky Mountain Dust Deposition - Cody C. Routson; Stéphanie H. Arcusa; Nicholas P. McKay; Jonathan T. Overpeck (Geophysical Research Letters)
Abstract Dust emissions from southwestern North America (Southwest) impact human health and water resources. Whereas a growing network of regional dust reconstructions characterizes the long‐term natural variability of dustiness in the Southwest, short‐term fluctuations remain unexplored. We present a 4.5‐millennia near‐annual record of dust mass accumulation rates from the southern Rocky Mountains, CO. Using microscanning X‐ray fluorescence and a geochemical end‐member mixing model, the record confirms dust increased with human disturbance beginning around 1880 CE, reversing a long‐term decreasing trend potentially related to changes in effective moisture, wind, and vegetation. However, increases in dust mass accumulation rates do not correspond to years or periods of drought, as characterized by tree rings. This result suggests sediment supply and transport mechanisms have a strong influence on dust deposition. The record shows the Southwest is naturally prone to dustiness; however, human disturbances have a large influence on dust emissions, which can be mitigated by changing land use.